ON MINIMALITY OF ONE SET OF BUILT-IN FUNCTIONS FOR FUNCTIONAL PROGRAMMING LANGUAGES - Martirosyan, G.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
The functional programming language, which uses the set car, cdr, cons, atom, eq, if_then_else of built-in functions is Turing complete (see [1]). In the present paper the minimality of this set of functions is proved.